Hubungan Antara Psychological Capital dengan Komitmen Organisasi Pada Pengurus Senior Ikatan Lembaga Mahasiswa Psikologi Indonesia 2024-2025: The Relationship Between Psychological Capital and Organizational Commitment in Senior Management of the Indonesian Psychology Student Association 2024-2025 - Dani Anur Salih; Widyastuti Widyastuti (Academia Open, 2025)
General Background: Organizational commitment is a critical construct in organizational psychology that reflects employees’ attachment and loyalty toward their institution. Specific Background: Psychological capital, which encompasses hope, self-efficacy, resilience, and optimism, has been recognized as a positive psychological resource associated with work-related attitudes. Knowledge Gap: However, empirical evidence examining the relationship between psychological capital and organizational commitment within the specific institutional context studied remains limited. Aims: This study aims to examine the relationship between psychological capital and organizational commitment among employees. Results: The findings indicate a significant positive relationship between psychological capital and organizational commitment, suggesting that higher levels of psychological capital are associated with stronger organizational commitment. Novelty: The study contributes by providing empirical evidence within the examined institutional setting, reinforcing the relevance of psychological capital in organizational contexts. Implications: These findings highlight the importance of developing employees’ psychological resources as part of organizational strategies to foster stronger commitment and sustainable organizational performance. Keywords: Psychological Capital, Organizational Commitment, Positive Organizational Behavior, Employee Attitudes, Quantitative Study Key Findings Highlights: Positive association identified between personal psychological resources and institutional attachment. Hope, resilience, optimism, and self-efficacy demonstrate meaningful linkage with work loyalty. Empirical evidence supports the relevance of positive organizational behavior constructs.